Formação de biofilmes e resistência a antimicrobianos de salmonella spp. isoladas em abatedouros avícolas - Mandelli, Jéssica Zolim Andreatto (2016)
Salmonella spp. Is a zoonotic pathogenic microorganism, often interconnected with outbreaks of food-borne diseases associated with the ingestion of food of poultry origin. It has an excellent ability to adapt to adverse environmental conditions and high biofilm formation capacity. Antimicrobial resistance is one of the greatest public health problems worldwide and isolated food microorganisms, especially Salmonella spp., may have a high occurrence of resistance, mainly due to the inappropriate use of these drugs. Based on the relevance of these themes, this dissertation was elaborated with a brief introduction and a scientific article. Chapter 1 presented the ability to form biofilms in polystyrene microplates under different incubation temperatures of 10 different serovars of Salmonella spp. and antimicrobial resistance commonly used in human clinical and / or broiler chickens and ESBL production by these serovars. These tests were performed using the antimicrobials: Ampicillin, Amoxicillin + Clavulanate, Aztreonam, Ceftazidime, Cefotaxime, Chloramphenicol, Gentamicin, Enrofloxacin, Sulfonamide and Tetracycline. It was possible to verify that only the antimicrobial Tetracycline was able to inhibit the microbial growth of 100% of the serovars tested. In serovars S. Infantis, S. Panama and S. Tennesse beta-lactamase enzyme production of extended spectrum was observed, through the formation of "ghost zones" or widening of the disc inhibition halo. All tested serovars adhered to polystyrene in at least one of the evaluated temperatures. At the temperature of 25°C, which mimics the ambient temperature, 50% of the isolates were moderately adherent. These results are of great importance due to the possibility of these serovars staying in food handling environments in the form of biofilms due to their increased ability to survive various temperatures and environmental conditions. Antimicrobials should be used with caution due to the resistance levels found. The absence of a methodology indicated by international bodies for the phenotypic evaluation of ESBL production by Salmonella spp. may be hindering comparison in research and underestimating its occurrence.